2017
DOI: 10.1111/appy.12302
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of online broadcasts of suicidality in China

Abstract: This study indicates that in China, suicide prevention programmes need to target internet users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Some researchers have estimated that depressive symptoms are one of the most important risk factors for suicide in the early phase of schizophrenia [187]. Depression can also lead to polypharmacy [188], impaired social functioning [189] and even reduced quality of life. Generally, comorbid depression in schizophrenia often hasn't been properly diagnosed which doesn't allow the implementation of its treatment among patients [1,11].…”
Section: Correlation-schizophrenia and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have estimated that depressive symptoms are one of the most important risk factors for suicide in the early phase of schizophrenia [187]. Depression can also lead to polypharmacy [188], impaired social functioning [189] and even reduced quality of life. Generally, comorbid depression in schizophrenia often hasn't been properly diagnosed which doesn't allow the implementation of its treatment among patients [1,11].…”
Section: Correlation-schizophrenia and Depressionmentioning
confidence: 99%
“…Mumtaz et al [188] analyzed reviews from both clinical and preclinical trials so as to define the effect of social isolation on neuropsychological disorders like depression or schizophrenia [199][200][201].…”
Section: Correlation-schizophrenia and Depressionmentioning
confidence: 99%
“…Today, the internet can provide new data sources because people record their lives in varying degrees on the website, and it has become an active interaction platform for young people, where they sometimes exchange thoughts portraying a susceptibility to suicidality [7]. Live streams of suicides are found on social media [8], and people often use such media to share their distress [7]. Indeed, young people are reluctant to disclose their suicidal signs in medical visits, but they are somehow willing to share these on social media platforms such as Facebook and Twitter [9].…”
Section: Introductionmentioning
confidence: 99%
“…To easily access and analyze data, in this study, we only focused on Sina Weibo rather than other internet platforms. According to a previous study [9], 30 relevant incidents that took place on Sina Weibo were identified. After that, the Weibo accounts associated with identified incidents were searched and found.…”
Section: Methodsmentioning
confidence: 99%
“…Since there is not yet a consensus on the definition of live-stream suicide, in this study, it is defined as making a self-disclosure of suicidality (including suicidal ideation, suicide plans and suicide attempts) on the internet without time delays. Between 2003 and 2016, at least 193 relevant incidents have been reported in China [9]. Of these incidents, the majority took place on social media sites.…”
Section: Introductionmentioning
confidence: 99%